2021
DOI: 10.1111/bju.15511
|View full text |Cite
|
Sign up to set email alerts
|

New recommendations to reduce unnecessary blood tests after robot‐assisted radical prostatectomy

Abstract: Radical prostatectomy (RP) is a standard treatment for men with localised prostate cancer. Robot-assisted RP (RARP) is associated with fewer intraoperative adverse events, reduced blood loss and lower complication rates compared to open and laparoscopic RP but delivers comparable oncological and functional outcomes [1]. Furthermore, the use of Enhanced Recovery after Surgery (ERAS) pathways for RARP, have improved patient recovery and experience, reducing costs and maintaining patient safety [2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Mostello et al examined the utility of routine postoperative sHgb measurements in patients undergoing primary total joint arthroplasty. 7 They found a transfusion rate of 0% in patients with a sHgb > 125 g/L preoperatively and > 100 g/L on POD 1. Eliminating subsequent measurements in these patients would have resulted in an overall reduction of 56% in sHgb measurements after POD 1 and significant savings.…”
Section: © 2022 Canadian Urological Associationmentioning
confidence: 95%
See 2 more Smart Citations
“…Mostello et al examined the utility of routine postoperative sHgb measurements in patients undergoing primary total joint arthroplasty. 7 They found a transfusion rate of 0% in patients with a sHgb > 125 g/L preoperatively and > 100 g/L on POD 1. Eliminating subsequent measurements in these patients would have resulted in an overall reduction of 56% in sHgb measurements after POD 1 and significant savings.…”
Section: © 2022 Canadian Urological Associationmentioning
confidence: 95%
“…By limiting investigations to at risk patients, Nathan et al demonstrated a reduction in routine postoperative bloodwork from 100% to 27% in patients undergoing robot assisted laparoscopic radical prostatectomy. 7 Benefits in their study included reduction in bloodwork related discharge delays from 6% to 0% with no missed postoperative complications during their study period.…”
Section: © 2022 Canadian Urological Associationmentioning
confidence: 99%
See 1 more Smart Citation